THE INFLUENCE OF PROMOTION, KOREAN WAVE AND BRAND AMBASSADOR ON THE BUYING INTEREST OF SCARLETT WHITENING PRODUCTS - Nurma Zulia Saputri; Farida Efriyanti (ZILLZELL MEDIA PRIMA, 2024)
The following research aims to find out how Promotion, Korean Wave, and Brand Ambassador influence buyers' Buying Interest in Scarlett Whitening Products. The study used quantitative types and primary data. The research sample of 70 respondents was taken from a population of 238 students of the Management Study Program class of 2020 Bandar Lampung University using the slovin formula. The test was performed using Multiple Linear Regression Analysis. Test the quality of the data obtained using Validity Test and Reliability Test. Then Test classical assumptions using normality, multicollinearity, and heteroscedasticity tests. The simultaneous significance test (f), the significance test of individual parameters (t), and the coefficient of determination test (R2) are used to test the hypothesis. The test used SPSS Statistics 29. The results of the analysis found that Promotions and Brand Ambassadors have a positive and significant influence on customer Buying Interest in Scarlett Whitening. And the Korean Wave has a negative and significant influence on customers' Buying Interest in Scarlett Whitening.